Approaches to Estimating the Health State Dependence of the Utility Function - Finkelstein, Amy; Luttmer, Erzo F. P; Notowidigdo, Matthew J (American Economic Review, 2009)
Approaches to Estimating the Health State Dependence of the Utility Function by Amy Finkelstein, Erzo F. P. Luttmer and Matthew J. Notowidigdo. Published in volume 99, issue 2, pages 116-21 of American Economic Review, May 2009